GASTRIC ADENOCARCINOMA DIAGNOSE : A CASE REPORT - Ida Bagus Komang Arjawa (E-Jurnal Medika Udayana, 2014)
Gastric cancer have become cancer number fourth from all incident of cancer andbecome the second killer cancer from all cancer. Undifined risk factor dan unspecificsign and symptom make most of this disease diagnosed in late phase. In this case report,a woman, 47 years old, single with main complaint nausea, vomitting and lose weightfrom six months ago. Diagnosed with gastric adenocarcinoma suspect IIIB stage.Diagnosing gastric cancer need completed and careful anamnesis and physicalexmination. Laboratory and other examination become main modality because a longtime of asymptomatic phase. Nowadays, endoscopy believed as a diagnostic methodswith high sensitivity and specificity in gastric adenocarcinoma followed by CT Scan todetect metastatic process to liver and lymph node. Finaly, histology study in laboratoriuhave become a gold standar to diagnose type of the neoplasm